2003
DOI: 10.1001/archinte.163.16.1939
|View full text |Cite
|
Sign up to set email alerts
|

The Ankle-Brachial Index in the Elderly and Risk of Stroke, Coronary Disease, and Death

Abstract: A low ABI is associated with risk of stroke or transient ischemic attack in the elderly. These results need to be confirmed in larger studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
188
3
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(212 citation statements)
references
References 34 publications
16
188
3
5
Order By: Relevance
“…To determine the ankle brachial index, BP was measured twice on both the arms and at both the ankles using an 8‐MHz Doppler pen probe and an ultrasonic Doppler flow detector (Park Medical Electronics Inc), as described elsewhere 14. Participants also underwent transthoracic echocardiography, and M‐mode images were used to determine measurements of LV structure.…”
Section: Methodsmentioning
confidence: 99%
“…To determine the ankle brachial index, BP was measured twice on both the arms and at both the ankles using an 8‐MHz Doppler pen probe and an ultrasonic Doppler flow detector (Park Medical Electronics Inc), as described elsewhere 14. Participants also underwent transthoracic echocardiography, and M‐mode images were used to determine measurements of LV structure.…”
Section: Methodsmentioning
confidence: 99%
“…Peripheral arterial disease (PAD) not only decreases quality of life due to intermittent claudication, but also, more importantly, is a powerful predictor of future cardiovascular and cerebrovascular events such as myocardial infarction, stroke, and death (Smith et al 1990, Criqui et al 1992, Murabito et al 2003. Previous clinical studies have shown that PAD is two-to three-fold more prevalent in men than in women (Dormandy & Rutherford 2000) and that low testosterone levels are associated with lower extremity PAD in elderly men (Tivesten et al 2007).…”
Section: Androgens and Peripheral Arterial Diseasementioning
confidence: 99%
“…Persons with PAD have 3‐ to 5‐fold higher mortality risk compared with those without PAD. Increased mortality is mainly driven by a higher cardiovascular disease (CVD) risk5, 6 and reflects the underlying systemic atherosclerosis process in PAD patients 7…”
Section: Introductionmentioning
confidence: 99%